Priority Areas Of Using Artificial Intelligence Technologies In The Digital Economy - Ibragimova Saodat Abdumuminovna (Global Scientific Publishing, 2025)
The article discusses the priorities of using artificial intelligence technologies in the context of digital transformation, the introduction of artificial intelligence technologies and their application, the possibilities of using digital information, issues of artificial intelligence technologies and their high quality
Keywords: digital economy; creative economy; digital transformation